A novel composite-diffusion brazing process based on transient liquid phase bonding of a Cf/SiC composite to Ti-6Al-4V. Issue 15 (15th October 2017) - Fan, Dongyu; Li, Changlin; Huang, Jihua; Yang, Jian; Cui, Bing; Wang, Wanli
Abstract: combining composite-brazing with transient liquid phase bonding (TLP), a novel process named composite-diffusion brazing was introduced to join Cf /SiC composite and Ti-6Al-4V at 930 °C for 30–120 min using (Ti-Zr-Cu-Ni)+16 vol%TiC. The added TiC particles distribute uniformly in the joints, which contributes to relax the residual stresses in the joints. The composition homogenization between interlayer and TC4 leads to the decrease of Cu and Ni contents in the interlayer, thereby the heat-resistance of joints has been improved significantly. When the dwelling time is 120 min, the melting-point of joints is raised to 1217 °C, which is 300 °C higher than that of filler. Besides that, the joints exhibit excellent high-temperature mechanical properties. The shear strengths of the joints at 800 °C reaches to 137.4 MPa, when the dwelling time is 90 min. Thus, the new composite-diffusion brazing process has the superiorities of both composite-brazing and TLP.